Combustion and emission characteristics of diesel engine fueled with diesel-like fuel from waste lubrication oil. (1st February 2017) - Wang, Xiangli; Ni, Peiyong
Highlights: 100% diesel-like fuel from waste lubricating oil was conducted in a diesel engine. Good combustion and fuel economy are achieved without engine modifications. Combustion duration of DLF is shorter than diesel. NOx and smoke emissions with the DLF are slightly higher than pure diesel. Abstract: Waste lubricant oil (WLO) is one of the most important types of the energy sources. WLO cannot be burned directly in diesel engines, but can be processed to be used as diesel-like fuel (DLF) to minimize its harmful effect and maximize its useful values. Moreover, there are some differences in physicochemical properties between WLO and diesel fuel. In order to identify the differences in combustion and emission performance of diesel engine fueled with the two fuels, a bench test of a single-cylinder direct injection diesel engine without any engine modification was investigated at four engine speeds and five engine loads. The effects of the fuels on fuel economic performance, combustion characteristics, and emissions of hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx) and smoke were discussed. The DLF exhibits longer ignition delay period and shorter combustion duration than diesel fuel. The test results indicate that the higher distillation temperatures of the DLF attribute to the increase of combustion pressure, temperature and heat release rate. The brake specific fuel consumption (BSFC) of the DLF compared to diesel is reduced by about 3% at 3000 rpm under light and medium loads. The DLF produces slightly higher NOx emissions at middle and heavy loads, somewhat more smoke emissions at middle loads, and notably higher HC and CO emissions at most measured points than diesel fuel. It is concluded that the DLF can be used as potential available fuel in high-speed diesel engines without any problems.